Disinfectant and Antimicrobial Susceptibility Studies of Staphylococcus aureus Strains and ST398-MRSA and ST5-MRSA Strains from Swine Mandibular Lymph Node Tissue, Commercial Pork Sausage Meat and Swine Feces - Ross C. Beier (MDPI AG, 2021)
Staphylococcus aureus (S. aureus) causes gastrointestinal illness worldwide. Disinfectants are used throughout the food chain for pathogenic bacteria control. We investigated S. aureus bioavailability in swine Mandibular lymph node tissue (MLT) and pork sausage meat (PSM), established susceptibility values for S. aureus to disinfectants, and determined the multilocus sequence type of MRSA strains. Antimicrobial and disinfectant susceptibility profiles were determined for 164 S. aureus strains isolated from swine feces (n = 63), MLT (n = 49) and PSM (n = 52). No antimicrobial resistance (AMR) was detected to daptomycin, nitrofurantoin, linezolid, and tigecycline, while high AMR prevalence was determined to erythromycin (50.6%), tylosin tartrate (42.7%), penicillin (72%), and tetracycline (68.9%). Methicillin-resistant S. aureus (MRSA) strains, ST398 (n = 6) and ST5 (n = 1), were found in the MLT and PSM, 4 MRSA in MLT and 3 MRSA strains in the PSM. About 17.5% of feces strains and 41.6% of MLT and PSM strains were resistant to chlorhexidine. All strains were susceptible to triclosan and benzalkonium chloride, with no cross-resistance between antimicrobials and disinfectants. Six MRSA strains had elevated susceptibilities to 18 disinfectants. The use of formaldehyde and tris(hydroxylmethyl)nitromethane in DC&R was not effective, which can add chemicals to the environment. Didecyldimethylammonium chloride and benzyldimethylhexadecylammonium chloride were equally effective disinfectants. ST398 and ST5 MRSA strains had elevated susceptibilities to 75% of the disinfectants tested. This study establishes susceptibility values for S. aureus strains from swine feces, mandibular lymph node tissue, and commercial pork sausage against 24 disinfectants. Since it was demonstrated that S. aureus and MRSA strains can be found deep within swine lymph node tissue, it may be beneficial for the consumer if raw swine lymph node tissue is not used in uncooked food products and pork sausage.